Alih Fungsi dan Perlindungan Lahan Pertanian: Pendekatan Sistem - Heryanto, Mahra Arari; Nugraha, Adi (Universitas Galuh, 2024)
Land conversion is a serious threat to national rice production. The conversion of agricultural land in West Java is very difficult to control. Conversion of agricultural land economically raises concerns that it endangers food security, reduces food production, reduces agricultural labour, and transforms the culture and livelihoods of local communities. This research intends to find out how the conversion of agricultural land affects the socio-economic life of farmer households and how land protection policies prevent the conversion of agricultural land. The research was conducted in West Java in three districts that have implemented LP2B protection policies (Subang District, Purwakarta District, and Tasikmalaya District) with a qualitative method using a system thinking approach. The results showed that land fragmentation triggered by narrow-land farming and social systems, coupled with economic and population growth pressures, accelerated the process of agricultural land conversion. This land conversion is a feedback or chain process that continues in the long term with high complexity from the micro (farmer households), meso (groups and territories), and macro (regions) levels. The incentives provided must be able to improve the welfare of farmer households in terms of production and markets.